Identification of novel aphid‐killing bacteria to protect plants. Issue 4 (1st August 2021) - Paliwal, Deepa; Hamilton, Amanda J.; Barrett, Glyn A.; Alberti, Fabrizio; van Emden, Helmut; Monteil, Caroline L.; Mauchline, Tim H.; Nauen, Ralf; Wagstaff, Carol; Bass, Chris; Jackson, Robert W.
Summary: Aphids, including the peach‐potato aphid, Myzus persicae, are major insect pests of agriculture and horticulture, and aphid control measures are limited. There is therefore an urgent need to develop alternative and more sustainable means of control. Recent studies have shown that environmental microbes have varying abilities to kill insects. We screened a range of environmental bacteria isolates for their abilities to kill target aphid species. Tests demonstrated the killing aptitude of these bacteria against six aphid genera (including Myzus persicae ). No single bacterial strain was identified that was consistently toxic to insecticide‐resistant aphid clones than susceptible clones, suggesting resistance to chemicals is not strongly correlated with bacterial challenge. Pseudomonas fluorescens PpR24 proved the most toxic to almost all aphid clones whilst exhibiting the ability to survive for over three weeks on three plant species at populations of 5–6 log CFU cm −2 leaf. Application of PpR24 to plants immediately prior to introducing aphids onto the plants led to a 68%, 57% and 69% reduction in aphid populations, after 21 days, on Capsicum annuum, Arabidopsis thaliana and Beta vulgaris respectively. Together, these findings provide new insights into aphid susceptibility to bacterial infection with the aim of utilizing bacteria as effective biocontrol agents. Abstract : An aphid‐feeding system was adapted to screen environmental bacteria for aphid‐killing properties and a selection of bacteria exhibited low‐to‐high killing effects in a range of aphid species including insecticide‐resistant clones. Pseudomonas fluorescens PpR24 demonstrated the best killing effect in vitro, whilst being able to survive on plant leaves over three weeks. Application of PpR24 to plants immediately prior to introducing aphids onto the plants led to a 50–60% reduction in aphid populations, after 21 days, on three different plant species.